2021
DOI: 10.5339/qmj.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of dialysis patients in Qatar: A retrospective epidemiologic study

Abstract: Background: End-stage kidney disease (ESKD) patients on maintenance renal replacement therapy (RRT) have far lower life spans than those of the general population. No previous studies have been performed to assess the mortality of dialysis patients in the State of Qatar. We designed this study to assess the mortality of dialysis patients in Qatar and the impact of dialysis modality. Methods: All chronic ambulatory dialysis patients (both on hemodialysis (HD) and peritoneal dialysis (PD) between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The two most prevalent comorbidities were diabetes and hypertension. However, the study found that MV calcifications were the most prevalent type of calcification, present in 55.5% of patients, followed by vascular calcification in other arterial vessels and aortic calcification (9) .…”
Section: Discussionmentioning
confidence: 79%
“…The two most prevalent comorbidities were diabetes and hypertension. However, the study found that MV calcifications were the most prevalent type of calcification, present in 55.5% of patients, followed by vascular calcification in other arterial vessels and aortic calcification (9) .…”
Section: Discussionmentioning
confidence: 79%
“…5 , 6 Other variables include decreased mortality in the ESKD population and increased occurrence of risk factors for ESKD (diabetes mellitus, hypertension, obesity, etc.). 7 - 9 In Qatar, only several government healthcare facilities run by the Hamad Medical Corporation have ever offered dialysis services. There were 250 PD patients (22%) and 900 HD patients (78%), using more than 80% of the available HD stations across the country as of January 1, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate is relatively low in the younger population. 15 Traditionally, anemia is managed in these centers by nephrologists. In 2015, HGH initiated a pilot program to evaluate the potential role of an anemia nurse manager (ANM) to improve anemia care in ambulatory dialysis centers.…”
Section: Introductionmentioning
confidence: 99%